2019
DOI: 10.1002/aoc.4831
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of heterobiaryls via Suzuki‐Miyaura coupling reaction of potassium aryltrifluoroborates with heteroaryl halides in aqueous systems

Abstract: A variety of heterobiaryl compounds have been synthesized by the Suzuki‐Miyaura coupling reactions of heteroaryl halides with potassium aryltrifluoroborates. Pd (OAc)2 was found to be highly efficient for the Suzuki‐Miyaura coupling reactions of various heteroaryl halides with potassium aryltrifluoroborates in aqueous systems, delivering the corresponding heterobiaryl compounds in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…The superior catalytic activity of Pd(OAc) 2 has been also shown in Suzuki–Miyaura reaction of aryltrifluoroborate derivatives in aqueous media. [ 33 ] Based on these results, for further studies, we chose Pd(OAc) 2 as a catalyst and 95% EtOH as a green and inexpensive solvent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The superior catalytic activity of Pd(OAc) 2 has been also shown in Suzuki–Miyaura reaction of aryltrifluoroborate derivatives in aqueous media. [ 33 ] Based on these results, for further studies, we chose Pd(OAc) 2 as a catalyst and 95% EtOH as a green and inexpensive solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the reaction is carried out in toluenewater with an inorganic base. [4,9,16,34] Although other solvents can be used as well (DMF, [35,36] dioxane, [37,38] or EtOH [33] ), it has been demonstrated that scope of boronic acids and thiophene substitution patterns is much more narrow. One notable exception is a method proposed by Varello et al [35] with catalysis by Pd(PPh 3 ) 4 in the presence of Na 2 CO 3 in DMF-water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22] The Suzuki-Miyaura reaction is usually performed by palladium catalyst. [23][24][25][26] Ni and Cu catalysts have also been used for this reaction but they have low yields. [27,28] Au catalysts have also exhibited high catalytic activity in the Suzuki reaction.…”
Section: Introductionmentioning
confidence: 99%